Features of Social Entrepreneurship Development in Primorsky Territory - Smitskih, Ksenia V. (International Journal of Criminology and Sociology, 2022)
Currently, the sphere of social entrepreneurship has low popularity among business representatives. Current trends are being actively discussed at the level of government bodies; however, the existing financial support and the low level of impact of state regulation instruments do not allow revealing the potential of social enterprise fully. Undoubtedly, social entrepreneurship is a relatively new phenomenon for Russia and has a number of features, conditioned, on the one hand, by the specifics of the national economy, and by the prevailing social relations on the other. The primary purpose of the study is to investigate features of social entrepreneurship development in Primorsky territory.